2019
DOI: 10.18697/ajfand.85.17425
|View full text |Cite
|
Sign up to set email alerts
|

Hazard analysis and critical control point plan for hazards in Ugandan amaranth vegetable value chain

Abstract: Currently, there is a high demand for amaranth due to its ability to withstand harsh climatic conditions, making it an ideal crop in the changing climate. There is also increased awareness and education on its nutritional and overall health benefits, and the availability of improved recipes. However, the presence of hazards can hinder the commercialisation of amaranth, which is in most cases traded informally. Food safety issues along the amaranth value chain should, therefore, be addressed to cope with both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Nonetheless, exceeding certain levels such as total aerobic count above 10000 CFU-g, Enterobacteriaceae 100 CFU-g, yeast and molds 100 CFU-g [25], AFB1 2 ppb, and total aflatoxin 4 ppb as permitted for dried fruits can suggest severe cases of poor hygiene and make the food product unfit for consumption [26]. Surpassing the set limits shows a failure to comply with good hygiene practice (GHP) and good manufacturing practice (GMP) as set by KEBS, WHO, and Codex Alimentarius guidelines on dried fruit [27]. Baobab pulp from informal processors had significantly higher (p ≤ 0:001, p ≤ 0:001) Enterobacteriaceae and yeast and molds counts (3:1 ± 0:70 log 10 CFU/g and 5:3 ± 0:11 log 10 CFU/g) than those from formal processors (0:7 ± 0:29 log 10 CFU/g and 3:1 ± 0:38 log 10 CFU/g), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, exceeding certain levels such as total aerobic count above 10000 CFU-g, Enterobacteriaceae 100 CFU-g, yeast and molds 100 CFU-g [25], AFB1 2 ppb, and total aflatoxin 4 ppb as permitted for dried fruits can suggest severe cases of poor hygiene and make the food product unfit for consumption [26]. Surpassing the set limits shows a failure to comply with good hygiene practice (GHP) and good manufacturing practice (GMP) as set by KEBS, WHO, and Codex Alimentarius guidelines on dried fruit [27]. Baobab pulp from informal processors had significantly higher (p ≤ 0:001, p ≤ 0:001) Enterobacteriaceae and yeast and molds counts (3:1 ± 0:70 log 10 CFU/g and 5:3 ± 0:11 log 10 CFU/g) than those from formal processors (0:7 ± 0:29 log 10 CFU/g and 3:1 ± 0:38 log 10 CFU/g), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest TAC contamination in candies was detected in samples collected from Mombasa County (5:4 ± 0:28 log 10 CFU/g), whereas the highest Enterobacteriaceae contamination was detected in samples collected from Kilifi county (3:3 ± 0:11 log 10 CFU/g) (Table 2). This could be linked to the type of water used during processing [27]. Groundwater supplies 50% of the water demand in the counties of Kilifi and Mombasa [31].…”
Section: Resultsmentioning
confidence: 99%
“…Heavy metals can also be absorbed by the aerial parts of plant leaves from dust and atmospheric precipitation in polluted areas, or from the fossil fuels used for heating, traffic density, fertilisers, and protective agents [82,83]. Vegetables may also be contaminated with trace metals from the water used by farmers to wash vegetables before they are placed on the market [84]. Vegetables grown in urban and peri-urban areas are more likely to be contaminated with high levels of heavy metals.…”
Section: Quality Of Fresh Vegetables In Farms and Markets In Ssamentioning
confidence: 99%
“…Meanwhile the concentrations of cadmium, zinc, copper, cobalt, manganese, and nickel were below the standards recommended by WHO. Aber et al [84] revealed that cadmium, lead, and mercury were major contaminants in vegetables sold on the streets of Nigeria. Lente et al [61] reported lead (1.8-3.5 mg/kg), contamination of vegetables irrigated with waste and ground water above the safe limits in Ghana.…”
Section: Quality Of Fresh Vegetables In Farms and Markets In Ssamentioning
confidence: 99%